Morpho-anatomical and physiological alterations of passion fruit fertilized with silicon - Costa, Bárbara Nogueira Souza; Costa, Irton de Jesus Silva; Dias, Gabrielen de Maria Gomes; Assis, Franscinely Aparecida de; Pio, Leila Aparecida Salles; Soares, Joyce Dória Rodrigues; Pasqual, Moacir (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effect of silicon fertilization on gas exchange, leaf anatomy, and ultrastructural characteristics of passion fruit (Passiflora edulis). The treatments comprised four concentrations of silicon (0, 0.28, 0.55, and 0.83 g per pot) at 1% silicic acid solution (SiO2.XH2O). This solution was applied around the stems of the plants. The first application was made 15 days after seedlings were transplanted. In total, three applications were made at 15-day intervals. The pots that constituted the control treatment received water in the same amount. After the final application, the plants were subjected to analyses of gas exchange, anatomical changes, and ultrastructural characteristics. The use of silicon promotes anatomical changes in passion fruit seedlings, such as increased adaxial epidermis thickness, reduced palisade parenchyma, and increased polar diameter/equatorial diameter ratio, which is related to stomata functionality. The concentrations of 0.55 and 0.83 g silicon per pot provide higher rates of photosynthesis, of transpiration, and stomatal conductance. The concentration of 0.83 g silicon per pot results in the greatest deposition of silicon in the abaxial epidermis of leaf surface.